The Way Ahead Meeting Canada's Productivity Challenge - Brzustowski, Tom (Governance Series, 2008)
Canada is a prosperous country, but this prosperity is being stressed by demographics, pressures on the public purse, and low productivity growth. To maintain the nation's high quality of life, prosperity must increase while remaining sustainable. Combining Tom Brzustowski's extensive knowledge of government, industry, and academia, The Way Ahead, articulates a strategy for moving the Canadian economy towards higher-value products based on research and development, describing the practical steps government, industry and academia must take to improve things in the short term and prepare strategically for the long term. He recommends increasing productivity growth by embracing an economy based on innovation, prioritizing research and development, marketing Canadian products internationally, and encouraging entrepreneurial activities in all sectors. Ultimately, increasing prosperity will require a new level of understanding, strategic coherence, and mutual support between the private and public sectors in Canada, a challenge that the author feels Canada is prepared to and absolutely must face.